(untitled) (The Research of Medical Science Review, 2025)
Tension neck syndrome is the one of the most common problem in recent eras due to increased use of mobile phone specially after the covid-19 pandemic and due to availability of all the tools needed in daily life. The tension neck syndrome is characterized by the neck pain sometimes radiating to neck, shoulders and upper back, mainly the involvement of trapezius and sternocleidomastoid muscle of neck, this pain is caused by the tension created due to the prolong flexed neck posture during mobile usage. Previous studies show that the force experienced by the cervical spine at different level of neck flexion is dramatically increased with the increased degree of flexion, normal weight of adult head is 10-12 pounds as the neck is flexed to 15 degrees the weight experienced by cervical spine (CS) is increased to 27 pounds and ultimately to 6o pounds at 60 degree of cervical flexion. To find out the prevalence of Tension Neck Syndrome among young mobile phone users. To assess the level of awareness/knowledge of tension neck syndrome and find association between time duration and neck disability. A cross-sectional study was conducted. For the study NDI questionnaire and mobile phone addiction scale MAS was used to collect data from the participants. The sample size was calculated by using RAO Software and data was analyzed by statistical package for social sciences SPSS 21.0 software to calculate the frequencies and association between variables. The results showed that 54% of the participants were having minimal or no difficulty 33% were having moderate disability and 11% were having severe disability and only 1% were in the crippled stage. The significance p value >0.001 shows the correlation between the time period of mobile phone usage and neck disability variable. Based on the results of the current investigation, about half of the individuals had neck issues. Neck issues were substantially correlated with smartphone addiction. Postural education and other initiatives to raise awareness of responsible smartphone use are advised. Participating actively in sports, social activities, and physical activity during free time will help university students reduce smartphone misuse and the effects it has on neck pain. Future research is necessary to determine how well neck posture-promoting strategies work to lessen smartphone addiction and misuse, which in turn helps to relieve neck pain